Chimeric antigen receptor T-cell therapy for multiple myeloma - Wang, Zehua; Chen, Chen; Wang, Lei; Jia, Yongxu; Qin, Yanru (Frontiers in Immunology, 2022)
Multiple myeloma (MM) is a malignant plasma cell disorder that remains incurable for most patients, as persistent clonal evolution drives new mutations which confer MM high-risk signatures and resistance to standard care. The past two decades have significantly refashioned the therapeutic options for MM, especially adoptive T cell therapy contributing to impressive response rate and clinical efficacy. Despite great promises achieved from chimeric antigen receptor T-cell (CAR-T) therapy, the poor durability and severe toxicity (cytokine release syndrome and neurotoxicity) are still huge challenges. Therefore, relapsed/refractory multiple myeloma (RRMM), characterized by the nature of clinicopathologic and molecular heterogeneity, is frequently associated with poor prognosis. B Cell Maturation Antigen (BCMA) is the most successful target for CAR-T therapy, and other potential targets either for single-target or dual-target CAR-T are actively being studied in numerous clinical trials. Moreover, mechanisms driving resistance or relapse after CAR-T therapy remain uncharacterized, which might refer to T-cell clearance, antigen escape, and immunosuppressive tumor microenvironment. Engineering CAR T-cell to improve both efficacy and safety continues to be a promising area for investigation. In this review, we aim to describe novel tumor-associated neoantigens for MM, summarize the data from current MM CAR-T clinical trials, introduce the mechanism of disease resistance/relapse after CAR-T infusion, highlight innovations capable of enhanced efficacy and reduced toxicity, and provide potential directions to optimize manufacturing processes.